Implementasi Budaya Kerja Islam dalam Pencapaian Visi Misi PT. Yotta Berkah Mulia - Al fadli Ramadhan; Dedy Irwansyah; Rahman Ambo Masse; A. Syathir Sofyan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to examine the implementation of Islamic work culture in achieving the vision and mission of PT.Yotta Berkah Mulia, its impact on company performance, and the challenges faced. This research employs a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The informants consist of management, employees, and customers.The results show that PT.Yotta Berkah Mulia applies Islamic work culture through the SIFAT principles (Shiddiq, Istiqamah, Fathanah, Amanah, Tabligh), implemented in weekly Tahsin programs, monthly Islamic studies, and the Jumat Berkah (Blessed Friday) program. This implementation positively impacts employee motivation, discipline, loyalty, and service quality, thereby supporting the achievement of the company's vision, “Inspiring People To Be Happy,” and its missions. The challenges include maintaining consistent employee participation, varying levels of understanding of Islamic values, and work target pressures.In conclusion, Islamic work culture plays a significant role in creating a harmonious work environment, improving performance, and strengthening the company's image as an ethical, religious, and trustworthy brand.